Preliminary study assessing remineralisation of early caries on posterior teeth using SoproLife® - Prema Sukumaran; Siti Nabila Sakroni; Nur Azhar Abu Bakar (Elsevier, 2019)
Purpose: The aim of this study was to assess the effectiveness of minimal intervention via fluoride therapy in management of early caries lesion with the aid of SoproLife®. Materials and methods: A total of 40 patients were recruited, (mean age = 23 years) and were assigned to low and moderate caries risk groups (n = 20). Eighty occlusal surfaces of posterior teeth were examined for early caries lesion visually and using SoproLife® at baseline and at a recall visit six months later. At baseline visit, patients were given oral hygiene education, fluoridated toothpaste for homecare and topical fluoride application. SoproLife® images acquired were analysed using Image J software version 1.50. Difference in the mean value of intensity of the red wavelength spectrum between baseline and recall visits, (ΔI), were analysed for both risk groups. ΔI for upper and lower first molar teeth were also analysed. Results: Results show no statistical difference for ΔI between low and moderate risk groups (p = 0.13). There is no statistical difference in ΔI within the low caries risk group (p = 0.42) but there is significant difference in the moderate risk group (p = 0.02). No statistically significant difference in ΔI value between upper first molars (UFM) (p = 0.80) and lower first molars (LFM) (p = 0.07) were detected. There was also no statistically significant difference in ΔI value within the upper and lower first molars (UFM: p = 0.31, LFM: p = 0.27). Conclusion: SoproLife® generated images did not show significant differences in remineralisation of early caries between low and moderate caries risk patients and between the upper first and lower first permanent molars in these patients. Keywords: CAMBRA, Caries, Caries risk assessment, Fluorescence, LIFEDT concept